Direct Atomic‐Level Imaging of Zeolites: Oxygen, Sodium in Na‐LTA and Iron in Fe‐MFI. (20th July 2020) - Mayoral, Alvaro; Zhang, Qing; Zhou, Yi; Chen, Pengyu; Ma, Yanhang; Monji, Taro; Losch, Pit; Schmidt, Wolfgang; Schüth, Ferdi; Hirao, Hajime; Yu, Jihong; Terasaki, Osamu
Abstract: Zeolites are becoming more versatile in their chemical functions through rational design of their frameworks. Therefore, direct imaging of all atoms at the atomic scale, basic units (Si, Al, and O), heteroatoms in the framework, and extra‐framework cations, is needed. TEM provides local information at the atomic level, but the serious problem of electron‐beam damage needs to be overcome. Herein, all framework atoms, including oxygen and most of the extra‐framework Na cations, are successfully observed in one of the most electron‐beam‐sensitive and lowest framework density zeolites, Na‐LTA . Zeolite performance, for instance in catalysis, is highly dependent on the location of incorporated heteroatoms. Fe single atomic sites in the MFI framework have been imaged for the first time. The approach presented here, combining image analysis, electron diffraction, and DFT calculations, can provide essential structural keys for tuning catalytically active sites at the atomic level. Abstract : Down to the atom : Through different imaging methods, electron microscopy can provide direct observation of oxygen atoms and sodium cations, pointing the way for the analysis of the local structure around heteroatoms in zeolite frameworks. The data provide clear evidence of Fe on tetrahedral sites within the MFI zeolite structure, clearly distinguished as single atoms.